Cellular and Molecular Mechanisms of Diuretic Plants: An Overview - Aparecida Livero, Francislaine; Vergutz Menetrier, Jacqueline; Luiz Botelho Lourenco, Emerson; Gasparotto Junior, Arquimedes (Current Pharmaceutical Design, 2017)
Heart failure, hypertension, cirrhosis and nephritic syndrome are among conditions that alter volume and composition of body fluids and are modulated by diuretics. Natural products are important source of diuretics and have been considered remarkable alternative with greater effectiveness and fewer side effects. However, many of these plants used in traditional medicine must be scientifically assessed about their efficacy and toxicity. Despite the large number of published articles claiming that plants or plant-derived components may act as diuretic agents, few studies have addressed the mechanism of action of medicinal plants. Thus, the aim of this review was to provide an overview of the current knowledge about the major cellular and molecular mechanisms of diuretic plants and/or their main compounds. Many well-established mechanisms (water channels, renal carriers, nitric oxide-cGMP and prostaglandin-cAMP pathways, renin-angiotensin and kinin-kallikrein systems, carbonic anhydrase, and osmotic effects), along with other newly identified targets, are connected to the diuretic activity of many natural products. However, the central path responsible for the activity of these agents remains unclear. Further studies may help clarifying the central role of each of these pathways in the pleiotropic response of these agents.
Keywords: hypertension